If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6b + 9p = 51 Solving 6b + 9p = 51 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-9p' to each side of the equation. 6b + 9p + -9p = 51 + -9p Combine like terms: 9p + -9p = 0 6b + 0 = 51 + -9p 6b = 51 + -9p Divide each side by '6'. b = 8.5 + -1.5p Simplifying b = 8.5 + -1.5p
| 20-B=5B+32 | | (f-1)-2f=-2(3+f) | | (-9n+(-2))-(-2n+5)= | | ln(x-5)-ln(x+2)=ln(x-10)-ln(x+10) | | -16=x-2 | | 24y+2x=48 | | 25(3)-5y=-25 | | 45x-24= | | 4x-104=180 | | 8-40=4a+60 | | 3r/1=4 | | 1.25q-12.5=8.35 | | -29b-84=b+336 | | b+11*3=-2 | | -8=4(y+1) | | (3x-8)(2x-4)= | | (-n+(-5))-(6n+(-6))= | | 8-15P=3P-10 | | 25x-5y=-25 | | 2.5x-6=-4-3.5x | | 14=x+-4+2x | | f=.50kv | | 4x-14=180 | | 9n^2=44n | | (3n+5(-5))-(2n+(-8))= | | f(x)=x^3-3x^2+3x-1 | | ln(x+1)=1.2+ln(x) | | -9=-5y+6 | | 74x=257+(-63x) | | 4u+4-54=14 | | 12=6y+12x | | 7x^2=74x |